Risiko Ergonomi Pekerja Perkantoran di Rumah Sakit X - Pratiwi, Tiara Amanda; Rosidati, Catur (Journal of Religion and Public Health, 2024)
Poor  working posture  and  non-ergonomic  chairs  for  office  workers  have  the potential to cause ergonomic hazards. This research aims to identify complaints and the level of ergonomic risk among office workers in the medical administration department of the X Hospital.  The  research  used  observation  and  interview  methods  on  10  respondents using  the  Nordic  Body  Map  (NBM)  and  the  Rapid  Office  Strain  Assessment  analysis technique.  (ROSA).  Based  on  the  research  results,  workers  with  adjustable  and  non-adjustable  chairs  reportedsignificant  pain  in  the  upper  neck,  lower  neck,  waist,  and buttocks.  Additional  complaints  were  noted  by  workers  using  non-adjustable  chairs, including considerable pain in the left shoulder, right shoulder, left calf, and right calf. A  high  level  of  ergonomic  risk  was  found  among  workers  using  non-adjustable  chairs with  a  score  of  6.  The  lowest  level  of  risk  was  found  among  workers  using  adjustable chairs with a score of 3. To reduce ergonomic complaints and lower ergonomic risk, it is necessary to designchairs and desks that match body posture, provide training on the correct use of office equipment, implement regular ergonomic assessments, and provide office facilities that support health.Keywords: Ergonomic, Office workers, Rapid Office Strain Assessment (ROSA)